Prevalence of sexual experience and associated factors of sexual debut among female vocational students in Nonthaburi. - Sara, N.; Roomruangwong, C. (Chulalongkorn Medical Journal, 2023)
Background : From previous studies, the number of female vocational students who had a sexual experience is about 40%, which is much higher than that of regular female high school students. These early sexual experiences have put vocational students at higher risk unfavorable consequences, e.g. HIV/ STD infections and unwanted pregnancies. However, the factors associated with these early sexual experiences have not been well-studied, Therefore we aimed to study these factors to provide strategies for prevention of unwanted pregnancies. Objectives : 1) To examine a prevalence of sexual experience among female vocational students in Nonthaburi Province. 2) To examine associated factors of sexual debut among female vocational students in Nonthaburi Province. Design : A cross – sectional descriptive study. Setting : Three vocational schools in Nonthaburi Province. Materials and Methods : Data were collected from 375 female vocational students from 3 vocation schools in Nonthaburi Province. Subjects were asked to complete 7 self-report questionnaires that included 1) personal and sexual information 2) A 22-item quiz on sexual knowledge 3) Questionnaire on attitude toward having friends of opposite-sex 4) Family relationships questionnaire 5) Friends influence questionnaire 6) Sexual risk behavior questionnaire, and 7) Rosenberg self-esteem scale. Descriptive statistics were used to find the prevalence of sexual experiences, and univariate analysis was used to identify factors associated with sexual debut. Results : The prevalence of sexual experience among this group of vocational students was 66.1 %. From logistic regression analysis revealed 8 factors namely; institution, people the students have been live with, attitude toward sex, female teacher with whom subjects had discussed about sex, male friends as person with whom subjects had discussed about sex, attitude toward sex, history of run away from home during adolescent and risk behaviors hight score. Conclusion : The prevalence of sexual experiences in this study is much higher than those of previous studies in vocational students. Awareness of risk factors may help us identify risk group and provide information for public health policy.